Dari Limbah ke Berkah: Briket Batok Kelapa sebagai Sumber Pendapatan Masyarakat Desa - Ilimu, Edi; Permana, Dian; Priyatmo, Yudi; Ansar; Nursamsir, Nursamsir; Yahyanto, Yahyanto; Musnajam, Musnajam; Husin, Husin; Andriani, Indri (PELITA NUSA TENGGARA, 2025)
The community service program in Gumanano Village, Mawasangka Subdistrict, Central Buton Regency aims to empower the community through the utilization of coconut shell waste into economically valuable products in the form of briquettes. Gumanano Village has abundant coconut potential; however, coconut shell waste has generally not been optimally utilized and is often discarded or burned, providing no added value. Through this program, training was provided along with the introduction of appropriate technology, including a coconut shell carbonizer, charcoal crusher, mixer, and briquette molding machine. The community was equipped with skills covering the entire production process, starting from raw material selection, processing, molding, to product packaging. The results of the program showed an increase in community knowledge and skills in managing coconut shell waste into environmentally friendly and marketable briquettes. In addition, the availability of production equipment supports work efficiency and product quality, thereby increasing the potential of briquettes as an alternative energy source as well as a new business opportunity for the community. Thus, this program is expected to improve household income, reduce environmental pollution, and promote economic independence for the people of Gumanano Village.